1988
DOI: 10.1063/1.340745
|View full text |Cite
|
Sign up to set email alerts
|

Mn magnetism and magnetic structures in RMn2

Abstract: Because of the tetrahedral arrangement of the Mn atoms in the Laves phases, the magnetic structures of the RMn2 are frustrated. To reduce this frustration, very unusual magnetic structures are stabilized with large crystallographic distortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…On the other hand, besides the Dy sample the direction of the magnetic moments in the hightemperature phase is the same in all samples, and it coincides with that in YMn 2 D 4. 3 . This suggests that in the temperature range T R ϽTϽT N the spin orientation is governed by Mn anisotropy.…”
Section: Reorientation Transitionsmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, besides the Dy sample the direction of the magnetic moments in the hightemperature phase is the same in all samples, and it coincides with that in YMn 2 D 4. 3 . This suggests that in the temperature range T R ϽTϽT N the spin orientation is governed by Mn anisotropy.…”
Section: Reorientation Transitionsmentioning
confidence: 95%
“…1,2 Secondly, in the C15 structure of the cubic Laves phases, the T atoms form a pyrochlore-like sublattice, which is known as fully frustrated for first-neighbor antiferromagnetic interactions. 3 In the pyrochlore lattice, no spin arrangement minimizes the free energy, which results in a fully degenerated spin-liquid state at Tϭ0 K. [4][5][6] Among the compounds where the transition metal carries an intrinsic moment, YMn 2 is the only one where antiferromagnetic long-range order appears in the frustrated Mn sublattice. The frustration yields a complicated helicoidal order associated with a structural distortion at the Néel transition.…”
Section: Introductionmentioning
confidence: 99%
“…A high degree of frustration arises for the Mn antiferromagnetism, leading to complicated magnetic structures (Ballou et al, 1988). Neutron-diffraction measurements have revealed that the low-temperature magnetic phase of TbMn 2 is metastable and poised between magnetic configurations with propagation vectors ( 2 3 2 3 0) and ( 1 2 1 2 1 2 ), respectively (Ballou et al, 1992).…”
Section: Related Electronic Magnetsmentioning
confidence: 99%
“…A large thermal expansion coefficient is also measured in the paramagnetic phase, which was interpreted in terms of a thermal increase of the mean-square local amplitude of Mn fluctuating moments [1]. As revealed by elastic neutron scattering on powdered samples the magnetic structures can be very complicated [2].…”
Section: Magnetic-ordered Phasesmentioning
confidence: 94%
“…The magnetocrystalline anisotropy associated with Mn is similarly far from being negligible. Complicated Néel orders (noncollinear, incommensurate, with weak-coupling features, multipropagating, …) are the results [2]. We mention in the following some of these magnetic-ordered phases.…”
Section: Introductionmentioning
confidence: 91%